American tripanosomiasis: a study on the prevalence of Trypanosoma cruzi and Trypanosoma cruzi-like organisms in wild rodents in San Luis province, Argentina Tripanosomiasis americana: um estudo sobre a prevalência do Trypanosoma cruzi e Trypanosoma cruzi-like em roedores silvestres da provincia de San Luis, Argentina - Ana María Brigada; Roberto Doña; Enrique Caviedes-Vidal; Edgardo Moretti; Beatriz Basso (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: Chagas disease is caused by Trypanosoma cruzi. Wild and perianthropic mammals maintain the infection/transmission cycle, both in their natural habitat and in the peridomestic area. The aim of this paper was to present the results from a study on wild rodents in the central and northern regions of San Luis province, Argentina, in order to evaluate the prevalence of this infection. METHODS: Sherman traps were set up in capture areas located between latitudes 32º and 33º S, and longitudes 65º and 66º W. The captured rodents were taxonomically identified and hemoflagellates were isolated. Morphological, biometric and molecular studies and in vitro cultures were performed. Infection of laboratory animals and histological examination of the cardiac muscle and inoculation area were also carried out. Parasites were detected in circulating blood in Calomys musculinus, Graomys griseoflavus, Phyllotis darwini and Akodon molinae. The parasites were identified using biological criteria. Molecular PCR studies were performed on some isolates, which confirmed the characterization of these hemoflagellates as Trypanosoma cruzi. RESULTS AND CONCLUSIONS: Forty-four percent of the 25 isolates were identified as Trypanosoma cruzi, and the remaining 56% as Trypanosoma cruzi-like. These findings provide evidence that wild rats infected with Trypanosoma cruzi and Trypanosoma cruzi-like organisms are important in areas of low endemicity. INTRODUÇÃO: A doença de Chagas é causada pelo Trypanosoma cruzi e os mamíferos periantrópicos e silvestres mantêm o ciclo de infecção/transmissão, tanto no ambiente natural, como no peridomicílio. O objetivo deste trabalho foi mostrar os resultados de um estudo de roedores silvestres do centro e norte da Província de San Luis, Argentina, para avaliar a prevalência da infecção. MÉTODOS: Estabeleceram-se lugares de caça com armadilhas tipo Sherman entre os 32º - 33º de latitude S e 65º - 66º de longitude W. Identificou-se taxonomicamente os roedores, isolou-se os hemoflagelados e fizeram-se ...